2019
DOI: 10.1007/s00228-019-02715-z
|View full text |Cite
|
Sign up to set email alerts
|

Premedication with intravenous steroids does not influence the incidence of infusion reactions following infliximab infusions in pediatric inflammatory bowel disease patients—a case-control study

Abstract: Purpose Infusion reactions (IR) are commonly described side effects of infliximab (IFX) infusions, often leading to discontinuation of IFX. This study aimed to investigate the influence of steroid premedication (PM) on incidence of IR in pediatric inflammatory bowel disease (PIBD) patients receiving IFX. Methods A case-control study in two tertiary centers in Amsterdam, The Netherlands, including PIBD patients receiving IFX. PM with steroids was part of standard care in one center (PM+) but not in the other ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 21 publications
5
7
0
Order By: Relevance
“…Eleven IRs were anaphylactic shock, and all of them resolved after steroid/antihistamine or adrenaline administration. Our results are comparable to the observations of other authors [18,19].…”
Section: Discussionsupporting
confidence: 93%
“…Eleven IRs were anaphylactic shock, and all of them resolved after steroid/antihistamine or adrenaline administration. Our results are comparable to the observations of other authors [18,19].…”
Section: Discussionsupporting
confidence: 93%
“…As both adult and pediatric studies were only cohort studies and not randomized trials, one could argue that the superiority of rapid infusions was the result of selection bias, as participants only received fast infusions after tolerating the first few regular infusions. This argument is not, however, supported by a recent study on IR in 226 children with IBD, which reported that the first infusion reaction on average happens at the sixth infusion (13).…”
Section: Discussionmentioning
confidence: 82%
“…17,18 A prior retrospective study of patients with inflammatory arthritis demonstrated that the premedication with methylprednisolone is effective in reducing the rates of arthralgia-myalgia syndrome after an iron dextran infusion. 18 In addition, Barton et al found that 87% of 135 patients with iron-deficiency anemia unresponsive to oral supplementation had no reaction to iron dextran infusion when premedicated with diphenhydramine, cimetidine, and dexamethasone. 17 Whether premedication is helpful in the prevention of iron infusion-related reactions remains an ongoing area of study, and will likely require further prospective evaluations.…”
Section: Discussionmentioning
confidence: 99%
“…These findings likely indicate the more widespread use of corticosteroid premedications among at risk patients. Premedications with methylprednisolone and an H 2 blocker before IV iron infusions are typically reserved for those patients who suspected to be at an increased risk of an allergic or infusion reaction, including patients with asthma or more than 1 drug allergy 17,18. A prior retrospective study of patients with inflammatory arthritis demonstrated that the premedication with methylprednisolone is effective in reducing the rates of arthralgia-myalgia syndrome after an iron dextran infusion 18.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation